Idiopathic Polyclonal Plasmacytosis Presenting as Fever of Unknown Origin - Vivek Pal Singh; Ashutosh Garg (Indian Journal of Medical Specialities)
An elderly male, after being flagged to have fever of unknown origin, was found to have plasmacytosis on bone marrow examination. On immunophenotyping, the proliferation was confirmed as polyclonal. No associated underlying condition such as infection or connective tissue disease was found. The importance of polyclonal plasmacytosis is discussed vis-a-vis the usual knee jerk reaction to diagnose multiple myeloma.